A flexible high-performance symmetric quasi-solid supercapacitor based on Ni-doped MnO2 nano-array @ carbon cloth. (10th July 2020) - Zhong, Rui; Xu, Mengyao; Fu, Ning; Liu, Rui; Zhou, An'an; Wang, Xiaodong; Yang, Zhenglong
Abstract: Carbon cloth (CC) is proved to be a very promising supercapacitor substrate due to its flexibility and excellent mechanical properties. In this paper, a simple and environmentally friendly hydrothermal reaction was used to construct petal-shaped Ni-doped MnO2 nano-array electrode material based on a flexible CC with strong adhesion, and PVA/Na2 SO4 gel electrolyte was coordinated to assemble flexible quasi-solid-state supercapacitor. Electrochemical tests manifested that the voltage window of Ni-doped MnO2 nano-array@CC electrode materials could reach 1.2 V, especially the area specific capacitance was up to 1398.8 mF cm −2  As an assembled device, the voltage window could reach 2.2 V, the volumetric capacitance was as high as 1022.08 mF cm −3, the energy density could reach 0.6871 mWh·cm −3, and the power density could be achieved as 31.43 mW cm −3, demonstrating good prospect in applications for flexible energy storage device. Graphical abstract: Image 1 Highlights: The Ni-doped MnO2 nano-array@carbon cloth was successfully prepared. The voltage window of Ni-doped MnO2 nano-array@carbon cloth electrode was 1.2 V. The area specific capacitance was 1398.8 mF cm −2 . A quasi-solid-state supercapacitor was assembled, the voltage window was 2.2 V. The assembled device volumetric capacitance was 1022.08 mF cm −3 .